Organisation and financing of the German health insurance - Becker, Ulrich (Delavci in delodajalci, 2016)
The author will try to explain the features of the German health insurance system, and to that end, proceed in two steps. The first consists of a rough overview of the system in general (chapter II.). The second step will lead to the main aspects of financing and organising the statutory health insurance (SHI), starting from the legal relations that have to be regulated and administered in order to make the SHI work (chapter III.).
Keywords: financiranje; Nemčija; socialna varnost; zdravstveno varstvo; zdravstveno zavarovanje